2014
DOI: 10.1098/rspb.2014.1980
|View full text |Cite
|
Sign up to set email alerts
|

Spectral tuning by opsin coexpression in retinal regions that view different parts of the visual field

Abstract: Vision frequently mediates critical behaviours, and photoreceptors must respond to the light available to accomplish these tasks. Most photoreceptors are thought to contain a single visual pigment, an opsin protein bound to a chromophore, which together determine spectral sensitivity. Mechanisms of spectral tuning include altering the opsin, changing the chromophore and incorporating pre-receptor filtering. A few exceptions to the use of a single visual pigment have been documented in which a single mature pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
158
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(168 citation statements)
references
References 47 publications
9
158
1
Order By: Relevance
“…Previous studies have hypothesized that cone opsin co-expression in humans could provide a developmental advantage (Xiao and Hendrickson, 2000). Alternatively, cone opsin co-expression in the cichlid fish Metriaclima zebra is thought to contribute to spectral tuning, although the λ max differences in these opsins is 35-48 nm (Dalton et al, 2014), far exceeding the 5 nm difference between rhodopsin and Rh1-2. However, rhodopsin also serves an important structural role in rod photoreceptors, where it is packed into the outer segments and forms an array of dimers (Fotiadis et al, 2003).…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have hypothesized that cone opsin co-expression in humans could provide a developmental advantage (Xiao and Hendrickson, 2000). Alternatively, cone opsin co-expression in the cichlid fish Metriaclima zebra is thought to contribute to spectral tuning, although the λ max differences in these opsins is 35-48 nm (Dalton et al, 2014), far exceeding the 5 nm difference between rhodopsin and Rh1-2. However, rhodopsin also serves an important structural role in rod photoreceptors, where it is packed into the outer segments and forms an array of dimers (Fotiadis et al, 2003).…”
Section: Discussionmentioning
confidence: 94%
“…This suggests that the large absorbance spectra in the adult LWS twin cones may derive from the co-expression of RH2Aβ with LWS (RH2Aβ with RH2Aα in the case of the MWS twin cone). The proposed dottyback scenario of coexpression involving two orthologous green genes (RH2A) with a difference in λ max of ∼10 nm and a longer shifted red gene (LWS), has recently been reported for the freshwater cichlid Metriaclima zebra (Dalton et al, 2014). In M. zebra, co-expressing multiple visual pigments within a single photoreceptor significantly enhances luminance discrimination, but the drawback seems to be a decrease in chromatic colour discrimination (Dalton et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The proposed dottyback scenario of coexpression involving two orthologous green genes (RH2A) with a difference in λ max of ∼10 nm and a longer shifted red gene (LWS), has recently been reported for the freshwater cichlid Metriaclima zebra (Dalton et al, 2014). In M. zebra, co-expressing multiple visual pigments within a single photoreceptor significantly enhances luminance discrimination, but the drawback seems to be a decrease in chromatic colour discrimination (Dalton et al, 2014). In support of these findings, we found a very similar pattern when modelling dottyback and coral trout visual tasks using the broad absorbance spectra instead of A 1 -based visual templates.…”
Section: Discussionmentioning
confidence: 99%
“…The gene repertoire and expression of opsins can vary according to the environment [37], and opsin expression can change in individuals in response to alterations in photic environment [24,26,27]. For instance, in the African cichlid fish Metriaclima zebra, lws and rh2aa opsins are coexpressed in double cones of the ventral but not the dorsal retina [25]. However, exposing developing embryos to light stimulus from below resulted in coexpression of lws and rh2aa throughout the adult M. zebra retina [38].…”
Section: Discussionmentioning
confidence: 99%
“…Opsin expression in the retina can change in response to different light stimuli [24][25][26][27]. Previous studies showed that rh2-1 and lws expression in Anableps occur exclusively in the ventral or dorsal regions of the retina, respectively [23].…”
Section: (D) Differential Opsin Expressionmentioning
confidence: 99%